Corporate social responsibility penetration, explicitness, and symbolic communication practices in Asia: A national business system exploration of leading firms in sustainability. (6th January 2020) - Conte, Francesca; Vollero, Agostino; Covucci, Claudia; Siano, Alfonso
Abstract: The study explores whether the penetration, explicitness, and symbolic corporate social responsibility (CSR) communication practices of organizations are associated with the characteristics of the countries to which they belong. By focusing on the national business systems (NBSs) of Asian countries, the study analyzes the websites of companies based in Japan, the Republic of Korea, Mainland China, and Hong Kong, to address strategic‐operational (penetration), discretionary‐non‐discretionary (explicitness), and substantial‐symbolic (symbolic practices) dimensions of CSR communication. The findings suggest that online CSR communication in Asian mirrors national business profiles. In particular, CSR penetration and explicitness in companies located in different Asian countries vary, whereas CSR symbolic communication does not appear to be related to the specifics of each NBS. The research extends the understanding of CSR communication in Asia based on the NBS theory. The findings can indicate to Asian managers how they can make CSR communication more effective, in terms of penetration and explicitness, and how to avoid symbolic CSR practices.